Formulasi dan Uji Fisik Ekstrak Biji Alpukat (Persea aericana Mill) dengan Cangkang Telur Sebagai Body Scrub - Fahamsya, Arifina; Listina, Osie (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Avocado seeds contain secondary metabolites such as alkaloids, flavonoids, saponins, tannins, and vitamin E, which are beneficial for skin care. A body scrub is a skin care preparation in the form of a liquid emulsion consisting of an oil phase and an aqueous phase, combined with abrasive particles that function to moisturize, cleanse skin pores, remove dead skin cells, and serve as a carrier for active compounds into the skin. This study aims to formulate a body scrub containing ethanol extract of avocado seeds that meets physical quality requirements and to determine its irritation potential. The ethanol extract of avocado seeds was obtained through maceration and remaceration methods. Four formulations were prepared: F0 (base), F1 (1%), F2 (5%), and F3 (10%). Physical evaluations included organoleptic testing, pH measurement, homogeneity, spreadability, adhesiveness, viscosity, and irritation testing. The results showed that the formulated body scrub met the physical quality requirements, with irritation scores ranging from 0.3 to 1.3, indicating very mild to mild irritation.